Analysis of Equipment Layout Factors in Oil and Gas Companies - Dedi Setiadi Miharja; Adi Herlambang (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
The equipment layout is one of the essential aspects of the smooth production of oil and gas companies. For this reason, this research investigates the determinants in determining the plan of oil and gas companies. Descriptive research methods used to describe any factors that become the layout. The survey conducted on 63 employees working in oil and gas companies. The results showed that the critical factors that formed the equipment layout were safety, easy operation facilities, easy maintenance facilities, preventing the spread of fire, consideration of expansion, and economic costs.